The lived experience of registered nurses educated in accelerated second degree bachelor of science in nursing programs: A hermeneutic phenomenological research study. - Hennessy, Lisa (Nurse Education in Practice, 2018)
Accelerated Second Degree Bachelor of Science in Nursing (ASDBSN) programs have proliferated in response to the ongoing and anticipated nursing shortages of the first decades of this century. While a number of studies have reported on the students enrolled in these programs, limited information exists regarding how nurses educated in these programs experience their nursing careers beyond the first two years of practice. This study was undertaken to explore the lived experience of registered nurses educated in an ASDBSN program. Using a hermeneutical phenomenological approach, twelve ASDBSN prepared nurses with greater than 2 years in nursing practice were interviewed with five different ASDBSN programs and seven different communities in the southwest United States represented. The interviews were face to face and occurred in a setting of the participants’ choice. A total of 4 themes were identified through the data analysis and a model of ASDBSN nursing practice was developed using the analogy of a river system. The themes included: Headwaters, Tributaries and Turbulence, The Rolling River, and The Delta. The results demonstrated that ASDBSN educated nurses are well socialized in the nursing profession and experience a high degree of job satisfaction and intent to stay in the profession.